(untitled) (Praxis Educativa, 2017)
The development of social and educational inclusion policies place members of schools board and other participants as protagonists of the materialization process of policies, i.e., their enactment. We inquire into the way in which they interpret and recreate the text of the policy, managing agreements influenced by their systems of beliefs and class positions. Generally, the inclusion logic of the policies and the values that back up traditional school grammar are in tension. In this work, we intend to reveal the different forms of enactment of the policies, and the beliefs or positions which back up the intermediation between the text and the policies materialization, due to their importance in the subjectivization process of those who receive them. For this purpose, we use empirical material composed of interviews made to school board members and teaching assistants from five schools in the province of Catamarca. In this research, we found intermediations and actions that question the model of rights acknowledgement of the policies and postulate meritocracy related to classic school grammar which provides order in the social and school expected way.